(untitled) (Medical Forum Monthly, 2024)
Objective: To study the clinical profile of angiofibroma, various conventional surgical approaches and the outcome of surgery. Design: Prospective, analytical study. Place and Duration of Study: This study was conducted at the Department of Otorhinolaryngology and Head & Neck Surgery, Bolan Medical Complex Hospital, Quetta from January2008 to December2012. Materials and Methods: This study included 31 patients of juvenile nasopharyngeal angiofibroma over a period of 5 years. All patients were treated by conventional surgical approaches following Fisch staging system. Twenty one (21) patients were operated by lateral rhinotomy approach, Three (3) patients by transpalatal approach, five (5) patients by Weber-Fergusson approach and two (2) by Mid-facial degloving approach. The patients were followed up for a period of three (3) years for any recurrence. Results: All patients were male with mean age 15.61±2.64 years. The patients presented with recurrent epistaxis, nasal obstruction and nasopharyngeal mass apart from other symptoms and signs. Majority of the patients (80.64%) came with stage II and IIIA disease. Lateral rhinotomy approach was used in majority of cases (67.74%). Recurrence was observed in 5 cases (16.12%). Recurrence rate was less (one out of 21cases) with lateral rhinotomy approach in comparison with other approaches. In transpalatal route recurrence was observed in two (2) cases out of three (3) cases, while in Weber-Fergusson approach it was one out of five (5) and in Mid-facial degloving it was one out of two (2) cases. Conclusion: Juvenile nasopharyngeal angiofibroma is a disease of male adolescents. The patient most commonly presents with recurrent epistaxis and nasal blockage with nasopharyngeal mass. Surgery is the treatment of choice. Lateral rhinotomy approach gives an excellent exposure for most of these tumours with less chance of recurrence.